2017
DOI: 10.1097/ico.0000000000001363
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Densitometry in Healthy Corneas and Its Correlation With Endothelial Morphometry

Abstract: Corneal densitometry might have potential to be used as an indicator of the health of corneal endothelium in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…Corneal densitometry assessments by using a Pentacam HR are able to detect various abnormalities in a wider zone than is a specular microscope. Corneal densitometry analysis may be employed to assess endothelial function in peripheral zones [2,4,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal densitometry assessments by using a Pentacam HR are able to detect various abnormalities in a wider zone than is a specular microscope. Corneal densitometry analysis may be employed to assess endothelial function in peripheral zones [2,4,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that corneal diseases such as keratitis [5], corneal epithelial oedema [6], Fuchs' endothelial corneal dystrophy [7] and keratoconus [8] can compromise corneal clarity, thus leading to an increase in corneal densitometry. The normal function of corneal endothelium and the regular arrangement of stromal layers play important roles in maintaining corneal clarity [9]. Otri AM [10] has noted that corneal densitometry can be used as an indicator of corneal heath.…”
Section: Introductionmentioning
confidence: 99%
“…Corneal densitometry values are expressed as the pixel luminance per unit volume in the Scheimpflug image, and are expressed in greyscale units (GSUs) (Figures A–B). The measurements range from zero (maximum transparency) to 100 (completely opaque cornea) according to the degree of backscattering light from the cornea …”
Section: Methodsmentioning
confidence: 99%
“…The corneal epithelial layer and the corneal endothelium are the major sources of corneal light scattering. Irregular interfaces between the corneal layers can cause glare and decreased visual acuity owing to increased light backscattering . Disruption of the corneal collagen matrix during oedema and the resultant corneal scarring can provoke an increase in corneal light scattering .…”
mentioning
confidence: 99%
See 1 more Smart Citation